(untitled) (TAJ: Journal of Teachers Association, 2009)
Abdominal lymphadenopathies are not uncommon in our population that we encounter during laparotomy done for various reasons. Many times patients present with chronic abdominal pain, even features of intestinal obstruction where mesenteric tuberculosis remains at the background. This study was done with an aim to see the clinico- pathological relation of incidental findings of abdominal lymphadenopathy found during laparotomy which was done for other causes. doi: 10.3329/taj.v21i2.3791 TAJ 2008; 21(2): 126-131